Southern Europe and the Eurozone Crisis Negotiations: Preference Formation and Contested Issues. Issue 1 (2nd January 2019) - Morlino, Leonardo; Sottilotta, Cecilia Emma
ABSTRACT: South European countries were severely hit by the eurozone crisis. Adopting the theoretical framework of prospect theory, this article conducts an empirical analysis of the interpretation of the situation by the South European political leaders in terms of gains and losses. After discussing the stances of South European countries vis-à-vis a number of contested issues which emerged during the 2010–2013 negotiations, the article goes on to provide a comparative account of the determinants of national preference formation with respect to the eurozone crisis reforms in Cyprus, Greece, Italy, Malta, Portugal and Spain, paying special attention to the relationship between governments and parliaments.